2016
DOI: 10.1177/0093854816677565
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Predictive Accuracy of the Structured Assessment of Protective Factors for Violence Risk in Criminal Forensic Evaluations

Abstract: Some actuarial and structured professional judgment (SPJ) risk-assessment instruments have already demonstrated their validity and predictive accuracy in expert criminal forensic evaluations. In contrast, little is known about the effectiveness of instruments identifying protective factors in risk of recidivism prediction. The present study was designed to evaluate the validity and predictive accuracy of the Structured Assessment of Protective Factors for Violence Risk (SAPROF) in 94 violent and sexual violent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
6
14
3
Order By: Relevance
“…These significant correlations were present in each setting, although a relatively poor correlation with HCR-20 in the general inpatient group stands out. These strong associations support the conceptual model underpinning the development of the SAPROF and fit with those reported elsewhere (Abbiati et al, 2016;Abidin et al, 2013: de Vries Robbe at al., 2011de Vries Robbe et al, 2015;Persson et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These significant correlations were present in each setting, although a relatively poor correlation with HCR-20 in the general inpatient group stands out. These strong associations support the conceptual model underpinning the development of the SAPROF and fit with those reported elsewhere (Abbiati et al, 2016;Abidin et al, 2013: de Vries Robbe at al., 2011de Vries Robbe et al, 2015;Persson et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…The relatively strong level of protective factors in the community sample here is actually lower than that reported for some inpatient forensic samples (Abidin et al, 2013;Davoren et al, 2013) but is comparable with another community sample surveyed by Yoon et al (2016), although the latter was an offender group. Both the forensic and general in-patient groups here are comparable with other forensic samples examined by Viljoen et al (2016) and Abbiati et al (2016) but somewhat stronger in terms of protective factors than others (de Vries Robbe et al, 2011; de Vries Robbe et al 2015).…”
Section: Discussionsupporting
confidence: 78%
“…A previous study had found good inter-rater reliability between these same researchers and good to excellent intraclass correlation coefficient values (Abbiati et al, 2017). Information was gathered from prison records and forensic assessment reports, both of which included evaluations, summaries of interviews with the offenders, sometimes summaries of interviews with the offender's family, and the courts' and/or judges' conclusions and recommendations about the risk of future violence or reoffending and about treatment plans.…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies show that actuarial risk assessment instruments are more predictive than SPJs (Hanson & Morton-Bourgon, 2004;Sjöstedt & Grann, 2002), others have found that SPJs outperform actuarial risk assessment instruments (Desmarais, Nicholls, Wilson, & Brink, 2012;deVries Robbé, deVogel, & Douglas, 2013;Pedersen et al, 2010). Similarly, some studies support the incremental validity of protective factors, especially when they are combined with other risk assessment instruments and used in secure hospital settings (Chu, Thomas, Ogloff, & Daffern, 2011;deVries Robbé et al, 2013;deVries Robbé, deVogel, Douglas, & Nijman, 2015), whereas others do not (Abbiati, Azzola, Palix, Gasser, & Moulin, 2017;O'Shea & Dickens, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While there is a dearth of research on protective factors that are not inverted risk factors (Polaschek, 2016), both conceptualizations have been supported in the literature. Divergent validity analyses between risk and protective factor measures have yielded significant inverse correlations between the two constructs (e.g., see Abbiati, Azzola, Palix, Gasser, & Moulin, 2017;Averill, 2016;Hanby, 2013;Persson, Belfrage, Fredriksson, & Kristiansson, 2017;Smeth, 2013;Tamatea &Wilson, 2009;. This supports the notion that protective factors are the opposite of risk factors.…”
Section: Incorporating Protective Factorsmentioning
confidence: 75%